2017
DOI: 10.47941/jacc.118
|View full text |Cite
|
Sign up to set email alerts
|

Financial Risk Management Strategies and the Growth of Microfinance Sector in Kenya

Abstract: Purpose: The purpose of this study was to investigate how financial risk management strategies lead to growth of MFI sector in Kenya.Methodology: The study adopted a correlation survey research design. The population of this study was fifty seven (57) MFIs. The sampling frame was the list of MFIs provided in the AMFI website www.amfikenya.com. A sample of thirteen (17) MFIs was selected using the random sampling approach. A questionnaire and an interview schedule were the main data collection tools. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Furthermore, according to Siminyu et al (2016), the ORM among managers may increase awareness and help overcome problems through education and promotion of cooperative microfinance efficiency. In addition, ORM policies and procedures may affect the growth of cooperative microfinance (Njuguna et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, according to Siminyu et al (2016), the ORM among managers may increase awareness and help overcome problems through education and promotion of cooperative microfinance efficiency. In addition, ORM policies and procedures may affect the growth of cooperative microfinance (Njuguna et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative microfinance organizations in Kenya, for example, should guarantee that solid operational risk management (ORM) is adopted and executed by overcoming a lack of understanding among implementing managers through training and risk management advocacy among their employees (Siminyu et al, 2016). Moreover, Njuguna et al (2017) revealed that sound operative risk management policies and procedures may have influenced cooperative microfinance's progress. Additionally, adherence to operating procedures in financial operations has significantly affected cooperative microfinance's growth.…”
Section: Operational Risk Management (Orm) and Performance Of Coopera...mentioning
confidence: 99%
See 1 more Smart Citation